Kemampuan Mengajar Pengajar BIPA (Bahasa Indonesia bagi Penutur Asing) dalam Pelatihan Tingkat Dasar se-Kota Bengkulu melalui Model Induktif Partisipatif - Arono Arono; Wisma Yunita; Ildi Kurniawan (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
Every teacher who is trained in teaching is influenced by the experience and intensity of practicing in teaching. However, in reality there are still teachers who sometimes have been teaching for a long time, but are still poorly trained in carrying out professional teaching practices, especially in teaching BIPA. This study aims to describe the teaching ability of BIPA teachers at the basic level with a participatory inductive model. This research method uses a qualitative descriptive method. Descriptively describes the mastery and teaching abilities of BIPA teachers at the basic level, while qualitatively it describes the processes and activities of the trainees through a participatory inductive model. The results of this study, namely the mastery of understanding BIPA material by training participants before training (average 65.12) and after training (85.68) increased by 21%. Aspects that become indicators of participants' mastery in mastering BIPA material, namely methodology, teaching materials, media, lesson plans, and evaluation. The teaching ability of participants in teaching BIPA at the basic level is good (4.09). However, there are several aspects that need to be observed in the ability to teach BIPA even though it is good, such as aspects of the assessment process (3.91) and reflection and summary (3.79). This success was carried out with a participatory inductive training model by following six stages, namely fostering intimacy, identification, formulation of goals and group discussions, program preparation, training process, and assessment of the training process. The participatory inductive model that is applied will produce better teaching skills if it is presented systematically or gradually or adapted to the training material.